Super-hydrophobic material, preparation method thereof, super-hydrophobic coating solution and super-hydrophobic coating
Patent Information
- Application Number
- CN202510530635.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本申请旨在解决上述技术问题,即,解决现有超疏水涂层随着使用时间的延长,涂层受损后疏水性下降而造成防覆冰功能下降的问题
[0022]1、本申请的超疏水材料的制备方法将低表面能物质溶液在加压和加热的条件下浸泡超疏水性的多孔二氧化硅,能够使较多的低表面能物质溶液顺利地渗透至超疏水性的多孔二氧化硅的孔隙中并将孔隙进行填充,有效提高孔隙的填充率以及超疏水性的多孔二氧化硅的孔隙内的低表面能物质的含量,从而在保证超疏水材料的现有超疏水性能的基础上提高超疏水材料的自修复能力,使具有该超疏水材料的超疏水涂层具有优异的自清洁及防覆冰性能。
Smart Images

Figure BDA0005376538600000191 
Figure BDA0005376538600000211
Abstract
Description
Technical Field
[0001] This application relates to the field of coating technology, specifically providing a superhydrophobic material and its preparation method, a superhydrophobic coating liquid, and a superhydrophobic coating. Background Technology
[0002] When photovoltaic modules are used outdoors, they must withstand extreme weather conditions such as high temperature, low temperature, humidity, sandstorms, rain and snow. Dust can easily accumulate on the front glass of the module, the anti-reflective coating on the surface can be damaged, and in high-latitude regions, ice can form on the glass surface during winter rain and snow. These are just some of the problems that affect the light transmittance of the front glass, which in turn affect the power generation efficiency of the photovoltaic module.
[0003] To address this issue, a superhydrophobic self-cleaning coating is typically applied to the anti-reflective coating surface of the front glass panel of the component. This effectively reduces dust accumulation on the glass surface. Simultaneously, the superhydrophobic surface exhibits lower ice adhesion and lower shear force for de-icing, effectively slowing down the icing rate on the coating surface and facilitating de-icing. However, after repeated cleaning or de-icing operations, the coating is prone to damage, gradually losing its self-cleaning and anti-icing functions.
[0004] Accordingly, a new technical solution is needed in this field to solve the above-mentioned technical problems. Summary of the Invention
[0005] This application aims to solve the above-mentioned technical problem, namely, to solve the problem that the hydrophobicity of existing superhydrophobic coatings decreases after the coating is damaged over time, resulting in a decline in anti-icing function.
[0006] In a first aspect, this application provides a method for preparing a superhydrophobic material, the method comprising: mixing a low surface energy material solution with superhydrophobic porous silica and heating and pressurizing the mixture for a preset time, so that the low surface energy material solution permeates into the pores of the superhydrophobic porous silica and fills the pores, thereby obtaining a superhydrophobic material; wherein the water contact angle of the superhydrophobic porous silica is greater than 150°, the porosity is 15% to 25%, and the pore diameter ranges from 5 nm to 15 nm.
[0007] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the pressure applied is 1-2 mPa; preferably 1.5 mPa; and / or the heating temperature is 50-60℃, preferably 60℃; and / or the preset time is 5-8 h; and / or the mass-to-volume ratio of the low surface energy substance to the solvent in the low surface energy substance solution is 1:(0.5-2) in g:ml; and / or the low surface energy substance in the low surface energy substance solution is one or more of siloxane-based organosilicon compounds, long-chain amines, and fluorine-containing compounds, or the surface energy of the low surface energy substance in the low surface energy substance solution is ≤30 mJ / m2 .
[0008] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the siloxane-based organosilicon compound includes at least polydimethylsiloxane; and / or, the long-chain amine includes at least octadecylamine; and / or, the fluorinated compound includes at least perfluorooctanoic acid and / or perfluorosilane.
[0009] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the low surface energy substance in the low surface energy substance solution is polydimethylsiloxane and / or perfluorosilane, and the solvent in the low surface energy substance solution is toluene; or, the low surface energy substance in the low surface energy substance solution is octadecylamine and / or perfluorooctanoic acid, and the solvent in the low surface energy substance solution is ethanol.
[0010] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the low surface energy substance in the low surface energy solution is polydimethylsiloxane and / or octadecylamine, and the mass-volume ratio of the low surface energy substance to the solvent in the low surface energy solution is 1:(1.5-2) in g:ml, preferably 1:1.7 in g:ml; or, the low surface energy substance in the low surface energy solution is perfluorosilane and / or perfluorooctanoic acid, and the mass-volume ratio of the low surface energy substance to the solvent in the low surface energy solution is 1:(0.5-1) in g:ml, preferably 1:0.83 in g:ml.
[0011] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the superhydrophobic porous silica is prepared by the following steps: (101) providing a mixture of a pore-forming agent, a silicon source, an initiator and a first solvent; (102) reacting the mixture to obtain silica nanoparticles; (103) removing the pore-forming agent from the silica nanoparticles to create pores on the silica nanoparticles to obtain porous silica nanoparticles; (104) modifying the porous silica nanoparticles with a silane coupling agent to obtain superhydrophobic porous silica.
[0012] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the volume-to-mass ratio of the silicon source, the initiator, and the pore-forming agent is (5-10):1:(0.3-0.5) in ml:ml:g; and / or, the volume ratio of the silicon source to the first solvent is (5-10):(80-120); and / or, the pore-forming agent is one or more of hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; and / or, the silicon source is tetraethyl orthosilicate; and / or, the initiator is ammonia; and / or, the first solvent is a mixture of anhydrous ethanol and water; and / or, the silane coupling agent is one or more of KH550, KH560, and KH570.
[0013] In the preferred embodiment of the above-mentioned method for preparing superhydrophobic materials, the concentration of ammonia is 25 wt%; and / or, the volume ratio of anhydrous ethanol to water is (5-10):1, preferably 10:1.
[0014] In a second aspect, this application provides a superhydrophobic material, which is prepared by the above-described method for preparing superhydrophobic materials. The superhydrophobic material comprises superhydrophobic porous silica and a low surface energy solution, wherein the low surface energy solution fills the pores of the superhydrophobic porous silica, and the water contact angle of the superhydrophobic material is greater than 150°.
[0015] In the preferred embodiment of the above-mentioned superhydrophobic material, the low surface energy material solution fills the pores of the superhydrophobic porous silica with a filling rate of 85% to 95%.
[0016] In a third aspect, this application provides a superhydrophobic coating liquid, which includes a crosslinking agent, a curing agent, a second solvent, and the superhydrophobic material described above.
[0017] In the preferred embodiment of the superhydrophobic coating solution described above, the mass ratio of the superhydrophobic material to the crosslinking agent is 1:(1-2), preferably 1:1.5; and / or, the mass ratio of the superhydrophobic material to the curing agent is 1:(0.1-0.2).
[0018] In the preferred embodiment of the above-mentioned superhydrophobic coating solution, the crosslinking agent is a mixed crosslinking agent of epoxy resin and polydimethylsiloxane; and / or, the second solvent is ethyl acetate; and / or, the curing agent is one or more of m-phenylenediamine, hexamethylenediamine, triethylenetetramine, and maleic anhydride.
[0019] In the preferred embodiment of the above-mentioned superhydrophobic coating solution, the mass ratio of the epoxy resin to the polydimethoxysilane is 1:(0.2-0.8), and preferably the mass ratio of the epoxy resin to the polydimethoxysilane is 1:0.5.
[0020] In a fourth aspect, this application provides a superhydrophobic coating, which is obtained by coating a substrate with the above-mentioned superhydrophobic coating liquid and then curing it. The superhydrophobic coating liquid is the superhydrophobic coating liquid described above. The water contact angle of the superhydrophobic coating is greater than 150°, and the water contact angle of the superhydrophobic coating is greater than or equal to 135° after being rubbed with steel wool 2000 times and exposed to light for 5 hours.
[0021] Compared with the prior art, the technical solution of this application has at least the following technical effects:
[0022] 1. The method for preparing the superhydrophobic material of this application involves immersing a low surface energy solution in superhydrophobic porous silica under pressure and heating conditions. This allows a large amount of the low surface energy solution to smoothly penetrate into and fill the pores of the superhydrophobic porous silica, effectively improving the pore filling rate and the content of low surface energy substances within the pores of the superhydrophobic porous silica. This enhances the self-healing ability of the superhydrophobic material while maintaining its existing superhydrophobic properties, resulting in a superhydrophobic coating with excellent self-cleaning and anti-icing properties.
[0023] 2. The superhydrophobic material prepared by the method of this application has a high pore filling rate. The pores of the porous silica contain a large amount of low surface energy substances. After the coating is worn, the low surface energy substances in the pores of the porous silica are released and diffused rapidly to cover the coating surface after being exposed to light, so that the superhydrophobic material can restore its superhydrophobic properties. Thus, the superhydrophobic coating containing the superhydrophobic material can restore its hydrophobic properties. The superhydrophobic coating can maintain good hydrophobic properties and anti-icing properties for a long time, thereby improving the effective service life of the superhydrophobic coating.
[0024] 3. The superhydrophobic coating made from the superhydrophobic material of this application has good self-healing ability, good anti-icing performance and long service life. Detailed Implementation
[0025] Preferred embodiments of this application are described below. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of this application and are not intended to limit the scope of protection of this application.
[0026] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0027] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0028] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0029] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0030] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.
[0031] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.
[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used in the following examples are commercially available unless otherwise specified.
[0033] This addresses the problem pointed out in this field that existing superhydrophobic coatings suffer from reduced hydrophobicity and decreased anti-icing function as the coating is damaged over time.
[0034] In a first aspect, this application provides a method for preparing a superhydrophobic material, which involves immersing a low surface energy solution in superhydrophobic porous silica under pressure and heating conditions. This allows a larger amount of the low surface energy solution to smoothly penetrate into and fill the pores of the superhydrophobic porous silica, effectively improving the pore filling rate and the content of low surface energy substances within the pores of the superhydrophobic porous silica. This enhances the existing superhydrophobic properties of the superhydrophobic material while improving its self-cleaning and anti-icing properties.
[0035] Specifically, the preparation method of the superhydrophobic material of this application includes: mixing a low surface energy material solution with superhydrophobic porous silica and heating and pressurizing the mixture for a preset time, so that the low surface energy material solution permeates into the pores of the superhydrophobic porous silica and fills the pores, thereby obtaining the superhydrophobic material. The superhydrophobic porous silica has a water contact angle greater than 150°, a porosity of 15%–25%, and a pore size range of 5 nm–15 nm.
[0036] Specifically, superhydrophobic porous silica can be purchased or prepared in-house. The porosity of the superhydrophobic porous silica used is 15%–25%, and the pore size is controlled to be 5nm–15nm. Under certain pressure, it can more smoothly fill the pores with a low surface energy solution, and can increase the relative content of low surface energy substances in the filled superhydrophobic porous silica, thereby enhancing the self-healing ability of the superhydrophobic material.
[0037] Preferably, the pressurization pressure is 1 to 2 mPa.
[0038] More preferably, the pressurization pressure is 1.5 MPa.
[0039] Preferably, the heating temperature is 50–60°C.
[0040] More preferably, the heating temperature is 60°C.
[0041] Preferably, the preset time is 5 to 8 hours.
[0042] By heating and pressurizing the reaction for 5–8 hours, the filling rate of the pores of superhydrophobic porous silica can be effectively improved by the low surface energy material solution, thereby giving the prepared superhydrophobic material good self-healing ability.
[0043] Preferably, the surface energy of the low surface energy substance in the low surface energy solution is ≤30 mJ / m 2 .
[0044] Preferably, the low surface energy substance in the low surface energy substance solution is one or more of the following: siloxane-based organosilicon compounds, long-chain amines, and fluorine-containing compounds.
[0045] Specifically, siloxane organic compounds include at least polydimethylsiloxane, long-chain amines include at least octadecylamine, and fluorinated compounds include at least perfluorooctanoic acid and / or perfluorosilanes.
[0046] In some embodiments, the low surface energy substance in the low surface energy substance solution is polydimethylsiloxane and / or perfluorosilane, and the solvent in the low surface energy substance solution is toluene.
[0047] In some embodiments, the low surface energy substance in the low surface energy substance solution is octadecylamine and / or perfluorooctanoic acid, and the solvent in the low surface energy substance solution is ethanol.
[0048] Preferably, the mass-to-volume ratio of the low surface energy substance to the solvent in the low surface energy substance solution is 1:(0.5-2) in g:ml, that is, low surface energy substance:solvent = 1g:(0.5-2)ml, or low surface energy substance:solvent = 2g:(1-4)ml.
[0049] In some embodiments, the low surface energy substance in the low surface energy substance solution is polydimethylsiloxane and / or octadecylamine, and the mass-volume ratio of the low surface energy substance to the solvent in the low surface energy substance solution is 1:(1.5-2) in g:ml.
[0050] In some further preferred embodiments, the low surface energy substance in the low surface energy substance solution is polydimethylsiloxane and / or octadecylamine, and the mass-to-volume ratio of the low surface energy substance in the low surface energy substance solution to the solvent is 1:1.7 in g:ml.
[0051] In some embodiments, the low surface energy substance in the low surface energy substance solution is a perfluorosilane and / or the perfluorooctanoic acid, and the mass-to-volume ratio of the low surface energy substance in the low surface energy substance solution to the solvent is 1:(0.5-1) in g:ml.
[0052] In some further preferred embodiments, the low surface energy substance in the low surface energy substance solution is perfluorosilane and / or perfluorooctanoic acid, and the mass-to-volume ratio of the low surface energy substance in the low surface energy substance solution to the solvent is 1:0.83 in g:ml.
[0053] Preferably, the superhydrophobic porous silica of this application is prepared by the following steps:
[0054] (101) Provide a mixture of pore-forming agent, silicon source, initiator and first solvent.
[0055] (102) React the mixture to obtain silica nanoparticles.
[0056] (103) Remove the pore-forming agent from the silica nanoparticles to create pores on the silica nanoparticles and obtain porous silica nanoparticles.
[0057] (104) The porous silica nanoparticles were modified by using a silane coupling agent to obtain superhydrophobic porous silica.
[0058] Preferably, the volume-to-mass ratio of silicon source, initiator and pore-forming agent is (5-10):1:(0.3-0.5) in ml:ml:g, that is, silicon source:initiator:pore-forming agent = (5-10)ml:1ml:(0.3-0.5)g.
[0059] More preferably, the volume-to-mass ratio of silicon source, initiator and pore-forming agent is 8:1:0.4 in ml:ml:g, that is, silicon source:initiator:pore-forming agent = 8ml:1ml:0.4g.
[0060] Preferably, the volume ratio of silicon source to first solvent is silicon source: first solvent = (5-10): (80-120).
[0061] More preferably, the volume ratio of silicon source to first solvent is silicon source: first solvent = 8:110.
[0062] Preferably, the silicon source is tetraethyl orthosilicate (TEOS).
[0063] Preferably, the initiator is ammonia water, wherein the concentration of ammonia water is 25 wt%.
[0064] Preferably, the pore-forming agent is one or more of hexadecyltrimethylammonium bromide (CTAB) and hexadecyltrimethylammonium chloride (CTAC).
[0065] Preferably, the first solvent is a mixture of anhydrous ethanol and water. The volume ratio of anhydrous ethanol to water is anhydrous ethanol:water = (5~10):1; more preferably, the volume ratio of anhydrous ethanol to water is anhydrous ethanol:water = 10:1.
[0066] Preferably, the silane coupling agent is one or more of KH550, KH560, and KH570.
[0067] The superhydrophobic porous silica prepared by the above-described method has uniform particle size, a water contact angle greater than 150°, a porosity of 15% to 25%, and a pore size range of 5 nm to 15 nm.
[0068] In a second aspect, this application provides a superhydrophobic material, which is prepared by the superhydrophobic material preparation method of the first aspect. The superhydrophobic material includes superhydrophobic porous silica and a low surface energy material solution, wherein the low surface energy material solution fills the pores of the superhydrophobic porous silica, and the water contact angle of the superhydrophobic material is greater than 150°.
[0069] Preferably, the low surface energy material solution fills the pores of the superhydrophobic porous silica with a filling rate of 85% to 95%.
[0070] The superhydrophobic material prepared by the method of this application has a high pore filling rate. The pores of the porous silica contain a large amount of low surface energy substances. After the coating is worn, the low surface energy substances in the pores of the porous silica are released and diffused rapidly to cover the coating surface after being exposed to light, so that the superhydrophobic material can restore its superhydrophobic properties. Thus, the superhydrophobic coating containing the superhydrophobic material can restore its hydrophobic properties. The superhydrophobic coating can maintain good hydrophobic and anti-icing properties for a long time, thereby improving the effective service life of the superhydrophobic coating.
[0071] In a third aspect, this application provides a superhydrophobic coating solution, which includes a crosslinking agent, a curing agent, a second solvent, and the superhydrophobic material provided in the second aspect above.
[0072] Preferably, the mass ratio of superhydrophobic material to crosslinking agent is superhydrophobic material: crosslinking agent = 1:(1~2).
[0073] More preferably, the mass ratio of superhydrophobic material to crosslinking agent is superhydrophobic material: crosslinking agent = 1:1.5.
[0074] Preferably, the volume-to-mass ratio of the second solvent to the total mass of the superhydrophobic material and crosslinking agent is (10-20) : (2-3) ml: g, that is, second solvent : (superhydrophobic material + crosslinking agent) = (10-20) ml : (2-3) g.
[0075] More preferably, the volume-to-mass ratio of the second solvent to the total mass of the superhydrophobic material and crosslinking agent is 15:2.5 in ml:g, that is, second solvent:(superhydrophobic material + crosslinking agent) = 15ml:2.5g.
[0076] Preferably, the mass ratio of superhydrophobic material to curing agent is 1:(0.1 to 0.2).
[0077] Preferably, the crosslinking agent is a mixed crosslinking agent of epoxy resin and polydimethylsiloxane. More preferably, the mass ratio of epoxy resin to polydimethylsiloxane is epoxy resin:polydimethylsiloxane = 1:(0.2-0.8), and even more preferably, the mass ratio is epoxy resin:polydimethylsiloxane = 1:0.5.
[0078] Preferably, the second solvent is ethyl acetate.
[0079] Preferably, the curing agent is one or more of m-phenylenediamine, hexamethylenediamine, triethylenetetramine, and maleic anhydride.
[0080] In a fourth aspect, this application provides a superhydrophobic coating, which is obtained by coating a substrate with a superhydrophobic coating liquid and then curing it. The water contact angle of the superhydrophobic coating is greater than 150°, and the water contact angle of the superhydrophobic coating is greater than or equal to 135° after being rubbed with steel wool 2000 times and exposed to light for 5 hours.
[0081] The following specific embodiments illustrate the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating of this application.
[0082] Example 1
[0083] The superhydrophobic material in this embodiment is prepared through the following steps:
[0084] S1: Provide a mixture of pore-forming agent, silicon source, initiator and first solvent: Mix 1 ml of 25 wt% ammonia, 8 ml of tetraethyl orthosilicate (TFOS), 0.4 g of cetyltrimethylammonium bromide (CTAB) with 110 ml of the first solvent to obtain a mixture, wherein the first solvent includes 100 ml of anhydrous ethanol and 10 ml of deionized water.
[0085] S2: React the mixture to obtain silica nanoparticles: Stir the mixture magnetically at room temperature for 12 hours to synthesize silica nanoparticles with a particle size of 50-80 nm.
[0086] S3: Remove the pore-forming agent from the silica nanoparticles: Centrifuge the porous silica nanoparticles at high speed, remove the supernatant, and then redisperse them with deionized water. Repeat the centrifugation 3 to 5 times to remove the hexadecyltrimethylammonium bromide (CTAB) from the silica nanoparticles to obtain porous silica nanoparticles.
[0087] S4: Modification of porous silica nanoparticles using a silane coupling agent: Porous silica nanoparticles were redispersed in 100g of an ethanol-water solution with a mass ratio of 9:1, and 4g of KH-550 was added. The mixture was heated and stirred in a water bath at 60°C for 3 hours to obtain a hydrophobically modified silica sol. The silica sol was centrifuged and washed three times with water to remove KH-550, resulting in superhydrophobic porous silica. Testing showed that the superhydrophobic porous silica prepared in this example had a water contact angle greater than 150°, a porosity of 23%, and pore sizes between 8nm and 12nm.
[0088] S5: A solution of superhydrophobic porous silica and a low surface energy substance was added to a high-pressure reactor to completely immerse the superhydrophobic porous silica in the low surface energy substance solution. The reactor was heated to 60°C and pressurized to 1.5 MPa for 8 hours. After the reaction was complete, the mixture was filtered, and the solid product was washed five times with deionized water to obtain the superhydrophobic material. Testing showed that the water contact angle of the superhydrophobic material prepared in this embodiment was greater than 150°.
[0089] The low surface energy substance in the low surface energy substance solution is octadecylamine, and its solvent is anhydrous ethanol. The mass-volume ratio of octadecylamine to anhydrous ethanol is 1g:1.7ml.
[0090] The superhydrophobic coating solution of this embodiment is prepared by the following steps: 1g of superhydrophobic material is added to 15ml of ethyl acetate, and after being ultrasonically dispersed evenly, 1g of epoxy resin, 0.5g of polydimethylsiloxane, and 0.1g of curing agent (m-phenylenediamine) are added and stirred evenly to obtain the superhydrophobic coating solution.
[0091] The mass ratio of epoxy resin to polydimethylsiloxane in the crosslinking agent is epoxy resin:polydimethylsiloxane = 1:0.5, the mass ratio of superhydrophobic material to crosslinking agent is superhydrophobic material:crosslinking agent = 1:1.5, and the volume-to-mass ratio of the second solvent to the total mass of the superhydrophobic material and crosslinking agent is 15ml:2.5g.
[0092] The superhydrophobic coating of this embodiment is prepared by the following steps: a 150nm thick coating is applied to the surface of a clean glass substrate by spin coating of superhydrophobic coating liquid, and cured at 180°C for 30 minutes to obtain the superhydrophobic coating.
[0093] Example 2
[0094] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the heating temperature in step S5 is different when preparing the superhydrophobic material.
[0095] In this embodiment, the heating temperature is 55°C.
[0096] Example 3
[0097] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the heating temperature in step S5 is different when preparing the superhydrophobic material.
[0098] In this embodiment, the heating temperature is 50°C.
[0099] Example 4
[0100] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the pressure applied in step S5 is different when preparing the superhydrophobic material.
[0101] In this embodiment, the pressurization pressure is 1 mPa.
[0102] Example 5
[0103] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the pressure and reaction time in step S5 are different when preparing the superhydrophobic material.
[0104] In this embodiment, the pressure is 2 mPa and the reaction time is 4 h.
[0105] Example 6
[0106] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the mass-to-volume ratio of octadecylamine to anhydrous ethanol in the low surface energy solution in step S5 is different when preparing the superhydrophobic material.
[0107] In this embodiment, the mass-to-volume ratio of octadecylamine to anhydrous ethanol is 1 g: 1.5 ml.
[0108] Example 7
[0109] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the mass-to-volume ratio of octadecylamine to anhydrous ethanol in the low surface energy solution in step S5 is different when preparing the superhydrophobic material.
[0110] In this embodiment, the mass-to-volume ratio of octadecylamine to anhydrous ethanol is 1g:2ml.
[0111] Example 8
[0112] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as in Example 1. The only difference between this embodiment and Example 1 is that the composition of the low surface energy material solution in step S5 is different when preparing the superhydrophobic material.
[0113] In this embodiment, the low surface energy substance in the low surface energy solution is polydimethylsiloxane, and the solvent is toluene.
[0114] Example 9
[0115] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the composition and ratio of the low surface energy material solution in step S5 are different when preparing the superhydrophobic material.
[0116] In this embodiment, the low surface energy substance in the low surface energy substance solution is perfluorooctanoic acid, and its solvent is anhydrous ethanol. The mass-to-volume ratio of perfluorooctanoic acid to anhydrous ethanol is 1g:0.83ml.
[0117] Example 10
[0118] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the composition and ratio of the low surface energy material solution in step S5 are different when preparing the superhydrophobic material.
[0119] In this embodiment, the low surface energy substance in the low surface energy substance solution is perfluorooctanoic acid, and its solvent is anhydrous ethanol. The mass-volume ratio of perfluorooctanoic acid to anhydrous ethanol is 1g:0.5ml.
[0120] Example 11
[0121] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the composition and ratio of the low surface energy material solution in step S5 are different when preparing the superhydrophobic material.
[0122] In this embodiment, the low surface energy substance in the low surface energy substance solution is perfluorooctanoic acid, and its solvent is anhydrous ethanol. The mass-volume ratio of perfluorooctanoic acid to anhydrous ethanol is 1g:1ml.
[0123] Example 12
[0124] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as in Example 1. The only difference between this embodiment and Example 1 is that the composition of the low surface energy material solution in step S5 is different when preparing the superhydrophobic material.
[0125] In this embodiment, the low surface energy substance in the low surface energy substance solution is perfluorosilane, and the solvent is toluene. The mass-to-volume ratio of perfluorosilane to toluene is 1g:0.83ml.
[0126] Example 13
[0127] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as in Example 1. The only difference between this embodiment and Example 1 is that the mass ratio of the superhydrophobic material to the crosslinking agent is different when preparing the superhydrophobic coating solution.
[0128] In this embodiment, the mass ratio of superhydrophobic material to crosslinking agent is 1:1. Specifically, the composition of the superhydrophobic coating solution is as follows: 1.5g superhydrophobic material, 1g epoxy resin, 0.5g polydimethylsiloxane, 15ml ethyl acetate, and 0.1g curing agent (m-phenylenediamine).
[0129] Example 14
[0130] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as in Example 1. The only difference between this embodiment and Example 1 is that the mass ratio of the superhydrophobic material to the crosslinking agent is different when preparing the superhydrophobic coating solution.
[0131] In this embodiment, the mass ratio of superhydrophobic material to crosslinking agent is 1:2. Specifically, the composition of the superhydrophobic coating solution is as follows: 1g superhydrophobic material, 1.33g epoxy resin, 0.67g polydimethylsiloxane, 15ml ethyl acetate, and 0.1g curing agent (m-phenylenediamine).
[0132] Example 15
[0133] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the mass ratio of epoxy resin to polydimethylsiloxane in the crosslinking agent is different when preparing the superhydrophobic coating solution.
[0134] In this embodiment, the mass ratio of epoxy resin to polydimethylsiloxane in the crosslinking agent is epoxy resin:polydimethylsiloxane = 1:0.2. Specifically, the composition of the superhydrophobic coating solution is as follows: 1g superhydrophobic material, 1.25g epoxy resin, 0.25g polydimethylsiloxane, 10ml ethyl acetate, and 0.1g curing agent (m-phenylenediamine).
[0135] Example 16
[0136] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as those in Example 1. The only difference between this embodiment and Example 1 is that the mass ratio of epoxy resin to polydimethylsiloxane in the crosslinking agent is different when preparing the superhydrophobic coating solution.
[0137] In this embodiment, the mass ratio of epoxy resin to polydimethylsiloxane in the crosslinking agent is epoxy resin:polydimethylsiloxane = 1:0.8. Specifically, the composition of the superhydrophobic coating solution is as follows: 1g superhydrophobic material, 0.83g epoxy resin, 0.67g polydimethylsiloxane, 10ml ethyl acetate, and 0.1g curing agent (m-phenylenediamine).
[0138] Example 17
[0139] The preparation processes of the superhydrophobic material, superhydrophobic coating solution, and superhydrophobic coating in this embodiment are the same as in Example 1. The only difference between this embodiment and Example 1 is that the mass ratio of curing agent to superhydrophobic material is different when preparing the superhydrophobic coating solution.
[0140] In this embodiment, the mass ratio of curing agent to superhydrophobic material is curing agent: superhydrophobic material = 0.2:1. Specifically, the composition of the superhydrophobic coating solution is as follows: 1g superhydrophobic material, 1g epoxy resin, 0.5g polydimethylsiloxane, 10ml ethyl acetate, and 0.2g curing agent (m-phenylenediamine).
[0141] Comparative Example 1
[0142] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this comparative example are the same as those in Example 1. The only difference between this example and Example 1 is that heating is not performed in step S5 when preparing the superhydrophobic material, and the room temperature is maintained at 25°C.
[0143] Comparative Example 2
[0144] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this comparative example are the same as those in Example 1. The only difference between this example and Example 1 is that no pressure is applied in step S5 when preparing the superhydrophobic material.
[0145] Comparative Example 3
[0146] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this comparative example are the same as those in Example 1. The only difference between this example and Example 1 is that, in the preparation of the superhydrophobic material, heating is not performed in step S5, the room temperature is maintained at 25°C, and no pressure is applied.
[0147] Comparative Example 4
[0148] The preparation processes of the superhydrophobic material, superhydrophobic coating liquid, and superhydrophobic coating in this comparative example are the same as those in Example 1. The only difference between this example and Example 1 is that step S5 is omitted, and the superhydrophobic porous silica obtained in step S4 is used as the superhydrophobic material.
[0149] Comparative Example 5
[0150] This comparative example only includes clean glass substrates.
[0151] Experimental Example 1
[0152] Pore filling rate: The pore filling rate of the superhydrophobic materials in Examples 1 to 17 and Comparative Examples 1 to 3 was determined by low-temperature nitrogen adsorption method. The results are shown in Tables 1 and 2. Specifically, the porosity x and y of the superhydrophobic porous silica before and after filling with a low surface energy solution were determined by low-temperature nitrogen adsorption method, where x is the porosity of the superhydrophobic porous silica and y is the porosity of the superhydrophobic material (i.e., the superhydrophobic porous silica after filling with a low surface energy solution). The pore filling rate was calculated as: Pore filling rate = (xy) ÷ x × 100%.
[0153] Anti-icing performance test of superhydrophobic materials: The superhydrophobic coatings of Examples 1 to 17 and Comparative Examples 1 to 4, as well as the glass substrate of Comparative Example 5, were tested. The water contact angle, freezing time at -10℃, ice layer adhesion strength at -10℃, ice layer shear strength at -10℃, freezing time at -20℃, ice layer adhesion strength at -20℃, and ice layer shear strength at -20℃ were tested. The test data are shown in Table 1.
[0154] Table 1. Anti-icing performance test data
[0155] The experimental data in Table 1 show that:
[0156] 1. The water contact angles of Examples 1 to 17 are basically the same as those of Comparative Examples 1 to 4, and other properties are also similar and much higher than those of Comparative Example 5. It can be seen that as long as superhydrophobic porous silica is used as a superhydrophobic material to form a superhydrophobic coating, the superhydrophobicity of the item can be improved. The anti-icing performance of the superhydrophobic coating is related to the superhydrophobicity. The better the superhydrophobicity, the better the anti-icing performance. The larger the water contact angle, the better the superhydrophobicity. Whether the porous silica is filled with low surface energy material has no effect on the initial hydrophobicity.
[0157] 2. The pore filling rates of the superhydrophobic materials in Examples 1 to 17 are significantly higher than those in Comparative Examples 1 to 3. This indicates that heating and pressurizing can improve the permeation efficiency of the low surface energy solution into the pores of superhydrophobic porous silica to fill the pores, thereby increasing the pore filling rate of the superhydrophobic material. Furthermore, as shown in Examples 1, 1, 2, and 3, the improvement effect is best when heating and pressurizing are applied simultaneously; heating or pressurizing alone has limited improvement effects.
[0158] 3. As can be seen from Examples 1, 13, and 14, the water contact angle of Example 1 is consistent with that of Example 13, which is better than that of Example 14. Therefore, it can be seen that in the superhydrophobic coating solution, increasing the ratio of superhydrophobic material to crosslinking agent can improve the hydrophobicity of the superhydrophobic coating. Therefore, it is preferable that the mass ratio of superhydrophobic material to crosslinking agent in the superhydrophobic coating solution is 1:1 to 2, and most preferably that the mass ratio of superhydrophobic material to crosslinking agent in the superhydrophobic coating solution is 1:1.5.
[0159] 4. As can be seen from Examples 1, 15, and 16, the water contact angle of Example 1 is better than that of Example 15, but worse than that of Example 16. Therefore, it can be seen that increasing the proportion of polydimethylsiloxane in the crosslinking agent can improve the hydrophobicity of the superhydrophobic coating. Therefore, the preferred mass ratio of epoxy resin to polydimethylsiloxane in the crosslinking agent is 1:0.2 to 0.8, and the most preferred mass ratio is 1:0.5.
[0160] Experimental Example 2
[0161] Verification of the self-healing function of the superhydrophobic coating: The superhydrophobic coatings in Examples 1 to 17 and Comparative Examples 1 to 4 were subjected to abrasion resistance tests. The test conditions were: 0000# steel wool, 1000g, rubbed for 500, 1000 and 2000 times respectively. The initial water contact angle of the superhydrophobic coating after abrasion and the water contact angle after 5 hours of light exposure were tested. The experimental results are shown in Table 2.
[0162] Table 2. Self-healing data of superhydrophobic coatings
[0163] The data in Table 2 shows that:
[0164] 1. Compared with Comparative Examples 1 to 4, Example 1 showed that the water contact angle before friction was basically the same. After 500 / 1000 / 2000 friction cycles, the initial water contact angle also showed a basically the same decreasing trend. However, after 5 hours of light exposure after friction, the water contact angle of Example 1 gradually recovered to a level close to that before friction. The superhydrophobic coating of Example 1 has a very good self-healing ability, so that the superhydrophobic coating after wear can restore its superhydrophobic properties. The water contact angles of Comparative Examples 1 to 3 recovered less, indicating a weak self-healing ability, but the degree of self-healing was low. Comparative Example 4 showed no recovery of the water contact angle. This is because, in the examples, a sufficient amount of low surface energy material solution was added and heated, stirred, and pressurized. The low surface energy material solution had a high permeability in the pores of the superhydrophobic porous silica. When the surface of the superhydrophobic coating was damaged, the low surface energy material within the pores of the broken silica particles was gradually released under light and diffused to the coating surface, thus achieving a self-healing effect. In Comparative Example 3, only immersion and permeation were performed without heating and pressurization, resulting in a low permeability of the low surface energy material solution and the worst self-healing effect. Comparative Example 1, which only applied pressure without heating, and Comparative Example 2, which only applied heat without pressurization, improved the permeability of the low surface energy material solution to some extent, but the improvement was limited, resulting in a poor self-healing effect.
[0165] Therefore, it can be seen that by filling the pores of superhydrophobic porous silica with a low surface energy solution, the superhydrophobic material can acquire self-healing ability, thus enabling the superhydrophobic coating prepared from the superhydrophobic material to have self-healing ability. In addition, by heating and pressurizing during the permeation process of the low surface energy solution, the filling effect of the low surface energy solution can be effectively improved, the pore filling rate of the superhydrophobic material can be increased, and the self-healing ability of the superhydrophobic material can be further improved.
[0166] 2. Comparing Examples 1 to 3, the water contact angles of the superhydrophobic coatings in Examples 1 to 3 are similar after 500 / 1000 / 2000 rubs. Therefore, the preferred heating temperature is 50℃~60℃.
[0167] 3. Comparing Examples 1, 4, and 5, the superhydrophobic coatings of Examples 1, 4, and 5 showed similar degrees of recovery of the water contact angle after 500 / 1000 / 2000 rubs. Therefore, it can be concluded that the preferred pressure is 1mPa to 2mPa and the preset time is 5 to 8h.
[0168] 4. Comparing Examples 1, 6 to 12, the superhydrophobic coatings of Examples 1, 6 to 12 showed similar recovery of water contact angle after 500 / 1000 / 2000 rubs. Therefore, it is preferable that the mass ratio of low surface energy material to solvent in the low surface energy material solution is low surface energy material: solvent = 1g: (0.5~2)ml.
[0169] 5. Comparing Examples 11, 13, and 14, the water contact angle before friction in Example 13 was the same as that in Example 1. However, after friction, the self-healing effect of Example 13 was weaker than that of Example 1. This was because the proportion of superhydrophobic material to crosslinking agent was increased, resulting in a reduction in crosslinking agent, which reduced the mechanical strength of the superhydrophobic coating, leading to more severe wear and a reduced self-healing effect. The water contact angle before friction in Example 14 was worse than that in Example 1, and the self-healing effect of Example 14 was weaker than that of Example 1 after friction. This was because the proportion of superhydrophobic material to crosslinking agent was reduced, resulting in a reduction in the amount of superhydrophobic material used, which weakened the initial hydrophobic effect of the superhydrophobic coating. In addition, it also reduced the content of low surface energy substances in the superhydrophobic coating, thereby weakening the self-healing effect of the coating. Therefore, in the superhydrophobic coating solution, the preferred mass ratio of superhydrophobic material to crosslinking agent is 1:1 to 2; the most preferred mass ratio is 1:1.5, so that the final superhydrophobic coating has good initial hydrophobic properties, self-healing ability and anti-icing properties.
[0170] 6. Comparing Examples 1, 15, and 16, the water contact angle before friction in Example 15 was worse than that in Example 1. However, after friction, the self-healing effect of Example 15 was close to that of Example 1. This is because the proportion of epoxy resin to polydimethylsiloxane in the crosslinking agent of the superhydrophobic coating solution decreased, resulting in a weakening of the initial hydrophobic effect of the coating. The water contact angle before friction in Example 16 was slightly increased compared to that in Example 1. Furthermore, the self-healing effect of Example 16 after friction was weaker than that of Example 1. This is because the proportion of epoxy resin to polydimethylsiloxane in the crosslinking agent of the superhydrophobic coating solution increased, resulting in insufficient mechanical strength of the superhydrophobic coating. Consequently, the coating was severely damaged after repeated friction, thus weakening the self-healing effect. Therefore, in the crosslinking agent of the superhydrophobic coating solution, the preferred mass ratio of epoxy resin to polydimethylsiloxane is 1:0.2 to 0.8; the most preferred mass ratio of epoxy resin to polydimethylsiloxane is 1:0.5, so that the final superhydrophobic coating has good initial hydrophobic properties and self-healing ability.
[0171] The technical solutions of this application have been described in conjunction with preferred embodiments. However, it will be readily understood by those skilled in the art that the scope of protection of this application is obviously not limited to these specific embodiments. Without departing from the principles of this application, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will all fall within the scope of protection of this application.
Claims
1. A method for preparing a superhydrophobic material, characterized in that, The preparation method includes: mixing a low surface energy material solution with superhydrophobic porous silica and heating and pressurizing the reaction for a preset time, so that the low surface energy material solution penetrates into the pores of the superhydrophobic porous silica and fills the pores to obtain a superhydrophobic material; The superhydrophobic porous silica has a water contact angle greater than 150°, a porosity of 15% to 25%, and a pore size range of 5 nm to 15 nm.
2. The method for preparing the superhydrophobic material according to claim 1, characterized in that, The pressurization pressure is 1–2 MPa; preferably 1.5 MPa. And / or, the heating temperature is 50-60°C, preferably 60°C; And / or, the preset time is 5 to 8 hours; And / or, the mass-to-volume ratio of the low surface energy substance to the solvent in the low surface energy substance solution is 1:(0.5-2) in g:ml; And / or, the low surface energy substance in the low surface energy substance solution is one or more of siloxane-based organosilicon compounds, long-chain amines, and fluorine-containing compounds; or, the surface energy of the low surface energy substance in the low surface energy substance solution is ≤30 mJ / m 2 .
3. The method for preparing the superhydrophobic material according to claim 2, characterized in that, The siloxane-based organosilicon compounds include at least polydimethylsiloxane; And / or, the long-chain amine comprises at least octadecylamine; And / or, the fluorinated compound includes at least perfluorooctanoic acid and / or perfluorosilane.
4. The method for preparing the superhydrophobic material according to claim 3, characterized in that, The low surface energy substance in the low surface energy substance solution is polydimethylsiloxane and / or perfluorosilane, and the solvent in the low surface energy substance solution is toluene; Alternatively, the low surface energy substance in the low surface energy substance solution is octadecylamine and / or perfluorooctanoic acid, and the solvent in the low surface energy substance solution is ethanol.
5. The method for preparing the superhydrophobic material according to claim 4, characterized in that, The low surface energy substance in the low surface energy substance solution is polydimethylsiloxane and / or octadecylamine, and the mass-volume ratio of the low surface energy substance in the low surface energy substance solution to the solvent is 1:(1.5-2) in g:ml, preferably 1:1.7 in g:ml; Alternatively, the low surface energy substance in the low surface energy substance solution is perfluorosilane and / or perfluorooctanoic acid, and the mass-volume ratio of the low surface energy substance in the low surface energy substance solution to the solvent is 1:(0.5-1) in g:ml, preferably 1:0.83 in g:ml.
6. The method for preparing the superhydrophobic material according to claim 1, characterized in that, The superhydrophobic porous silica is prepared by the following steps: (101) Provide a mixture of pore-forming agent, silicon source, initiator and first solvent; (102) React the mixture to obtain silica nanoparticles; (103) Remove the pore-forming agent from the silica nanoparticles to create pores on the silica nanoparticles to obtain porous silica nanoparticles. (104) The porous silica nanoparticles were modified by using a silane coupling agent to obtain superhydrophobic porous silica.
7. The method for preparing the superhydrophobic material according to claim 6, characterized in that, The volume-to-mass ratio of the silicon source, the initiator, and the pore-forming agent, expressed in ml:ml:g, is (5-10):1:(0.3-0.5). And / or, the volume ratio of the silicon source to the first solvent is (5-10):(80-120); And / or, the pore-forming agent is one or more of hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; And / or, the silicon source is tetraethyl orthosilicate; And / or, the initiator is ammonia; And / or, the first solvent is a mixture of anhydrous ethanol and water; And / or, the silane coupling agent is one or more of KH550, KH560, and KH570.
8. A superhydrophobic material, characterized in that, The superhydrophobic material is prepared by any one of claims 1 to 7, wherein the superhydrophobic material comprises superhydrophobic porous silica and a low surface energy material solution, the low surface energy material solution filling the pores of the superhydrophobic porous silica, and the water contact angle of the superhydrophobic material is greater than 150°.
9. The superhydrophobic material according to claim 8, characterized in that, The low surface energy material solution fills the pores of the superhydrophobic porous silica with a filling rate of 85% to 95%.
10. A superhydrophobic coating solution, characterized in that, It includes a crosslinking agent, a curing agent, a second solvent, and the superhydrophobic material as described in claim 9.
11. The superhydrophobic coating solution according to claim 10, characterized in that, The mass ratio of the superhydrophobic material to the crosslinking agent is 1:(1-2), preferably 1:1.5; And / or, the mass ratio of the superhydrophobic material to the curing agent is 1:(0.1 to 0.2).
12. The superhydrophobic coating solution according to claim 10, characterized in that, The crosslinking agent is a mixed crosslinking agent of epoxy resin and polydimethylsiloxane; And / or, the second solvent is ethyl acetate; And / or, the curing agent is one or more of m-phenylenediamine, hexamethylenediamine, triethylenetetramine, and maleic anhydride.
13. The superhydrophobic coating solution according to claim 12, characterized in that, The mass ratio of the epoxy resin to the polydimethoxysilane is 1:(0.2-0.8), preferably 1:0.
5.
14. A superhydrophobic coating, characterized in that, The superhydrophobic coating is obtained by coating a substrate with a superhydrophobic coating liquid and then curing it. The superhydrophobic coating liquid is any one of claims 10 to 13. The water contact angle of the superhydrophobic coating is greater than 150°, and the water contact angle of the superhydrophobic coating is greater than or equal to 135° after being rubbed with steel wool 2000 times and exposed to light for 5 hours.